Cindy Ellen : a wild western Cinderella - Lowell, Susan, 1950-; Manning, Jane K. (New York : Scholastic, 2001)
Cindy Ellen loses one of her diamond spurs at the square dance in this wild western retelling of the classic Cinderella story.
Keywords: Fairy tales -- Juvenile fiction